Immunization errors of COVID-19 vaccines in Minas Gerais - Wiara Viana Ferreira; Thayane Ingrid Xavier de Andrade; Thays Cristina Pereira Barbosa; Rillary Carvalho dos Santos; Stênio Henrique Oliveira; Vinícius Carvalho Guimarães; Eliete Albano de Azevedo Guimarães; Valeria Conceição de Oliveira (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to analyze immunization errors related to COVID-19 vaccines in Minas Gerais. Methods: a descriptive epidemiological study, carried out in Minas Gerais with data from e-SUS Notifica in 2021. Descriptive analysis and calculation of the incidence rate by health macro-regions of the state were performed. Results: of the 853 municipalities, only 381 (44.7%) reported some immunization error, totaling 2,724 reports. The incidence of errors reported in the state was 7.8/100 thousand doses applied, with the Vale do Aço macro-region (14.4/100 thousand) having the highest incidence. The most frequent error was the type of vaccine used (37.3%), and the Pfizer vaccine had the lowest incidence of error. Conclusions: the COVID-19 vaccine immunization errors reported in Minas Gerais point to the heterogeneity in incidence rates in the various macro-regions of the state, in addition to the underreporting of these errors.